Imagery And Moral Values Found In “Poems For Palestine” By Palestinian Poets - Ilahi, Ilham; Efendi, Dedi; Afrilesa, Rini (Krinok:Jurnal Linguistik Budaya, 2025)
This research analyzed about imagery and moral values in three poems of Poems for Palestine by Palestinian Poets. The purposes of this research are to describe the kinds of imagery and the kind of moral values in three poems of “Poems for Palestine by Palestinian Poets”. In this research, the writer used the descriptive qualitative method which was proposed by Strauss and Corbin (1998:11). They state that qualitative research is achieved not by means of quantification or statistical technique to analysis the data. The data is analyzed through some ways: identifying, classifying, analyzing and making conclusion. In this reasearch, the writer used theory of imagery by Perrine (1992) and theory of moral values by Hornby (2010). The result of this research are the writer found about 17 imagery data and followed by 17 data of moral values of the research. All of the data analyzed in those three poems of Poems for Palestine by Palestinian Poets.The 17 data of imagery that the writer found in those three Poems for Palestine by Palestinian Poets, the visual imagery is the dominant imagery in the poems. It is because of the authors really want the world pay attention the condition of the Palestine today. The displacement and destruction of Palestine is seen by many as a deliberate attempt to erase the Palestinian presence and identity from the region. The loss of land and the ongoing displacement of Palestinians are become the first target of Israel and allies. 17 data of moral values that found in poems dominated by 10 data of sympathetic to others. Being sympathetic to others in the poem means feeling and showing understanding and concern for Palestine suffering or misfortune. It involves recognizing and caring for the Palestinian feelings, even if you haven't experienced the same situation